DEVELOPMENT OF CALM (CASE-BASED ADVANCED LEARNING FOR PAIN MANAGEMENT) TO IMPROVE THE ATTITUDES, KNOWLEDGE, AND BEHAVIOR OF FINAL-YEAR NURSING STUDENTS ON PAIN MANAGEMENT - Rondhianto Rondhianto; Ika Adelia Susanti; Muhamad Zulfatul A’la; Farida Nur Qomariyah (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2026)
Background: Pain is a primary complaint among patients in healthcare services. The failure in pain management can increase morbidity and mortality rates. There is a need to improve nursing students' competencies through innovative Web-Based Learning (WBL) models, which leverage technology to create a comprehensive and interactive learning environment. This study aims to develop CALM (Case-based Advanced Learning for Pain Management) to enhance the attitudes and knowledge of final-year nursing students regarding pain.Method: The research design used was Research and Development (R & D), involving final-year nursing students from the Faculty of Nursing, University of Jember, who met the inclusion and exclusion criteria. The sampling technique used was purposive sampling. The research instruments used were the Knowledge and Attitude Survey Regarding Pain (KASRP), Nurse Behavior Questionnaire in Pain Management (NBQ-P), Focus Group Discussion (FGD) guide, and System Usability Scale (SUS). Data analysis was performed using descriptive statistical analysis.Results: The results of the study indicated that the knowledge and attitudes of final-year nursing students regarding pain fall into the low category (53.8%). In terms of pain management behavior, the majority of respondents were in the good category (55.90%). The development of CALM learning media resulted in six modules to be developed: pain assessment and evaluation; pain pharmacology; non-pharmacological interventions; pain in special populations; and cultural, spiritual, and ethical aspects of pain management. The feasibility test of CALM learning media showed positive results.Conclusions: The development of CALM learning media was highly accepted, functions optimally, facilitating access to pain-related information, and aligning with previous evidence regarding the effectiveness of e-learning and interprofessional curricula, which have the potential to enhance knowledge, assessment skills, and learning satisfaction among students